Which is it. new world of teaching machines or brave new teaching machines - Morello, Ted. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1961)
A program consists of instructional material designed to lead a pupil almost unaided and without error to a preselected level of learning by what amounts to a pavlovian stimulus-response-toward pattern. Behind any program lies the theory that the material must start with something familiar to the student and progress with increasing difficulty through steps so small that the student can move forward alone with reasonable assurance of responding correctly. A teaching machine may range from a device little more sophisticated than the traditional student work book to a complex mechanical and/or electronic tutor that presents written and audiovisual material. Programed teaching is effective. Programed teaching must also be efficient, material should be prepared that will guide a pupil in the desired direction without meaningless departures. A sound program is one that has been prepared meticulously and tested regularly. Programing falls into two broad categories--linear in which the student is guided step by step toward a correct response and is even prompted with thinly veiled hints, and branching in which the student who responds with the right answer moves along the trunk route to the next question, if he is wrong he is detoured over remedial material. Programs are valuable because they can liberate teachers from the drudgery of purely mechanical instruction. This article is published in, "the world of teaching machine," 1961.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Instructional Materials; Learning Activities; Patterned Responses; Programed Instruction; Teaching Machines; Teaching Methods